Asymmetric general oligopolistic equilibrium - Ansgar F. Quint; Jonas F. Rudsinske (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2020)
We develop an asymmetric general oligopolistic equilibrium (AGOLE) model, which extends the range of possible applications in general oligopolistic equilibrium modelling. The AGOLE allows to incorporate endogenous and asymmetric marginal utilities of income across countries.As a first exemplary application, we analyze the effects of asymmetric labor market policies. When one country increases its labor supply per capita, it is optimal for its firms to supply a part of the additional production to the other country at reduced prices to artificially inflate domestic prices. This results in a spillover effect letting consumption increase abroad due to a change in the terms of trade. In AGOLE, oligopolistic competition can induce asymmetric price reactions that shift real income and demand between the two countries. We argue that incorporating this cross-country demand channel is crucial for analyzing asymmetric countries or policies in presence of firms with market power.
Keywords: F12; D51; L13; F16; D33; 330; general oligopolistic equilibrium; strategic trade; international trade and labor market interactions; factor income distribution